Chef tako (food franchise) / Cik Muhamad Zafri Che Sabudin ...[et al.] - Zulkafli, Muhammad Nazmi; Abdullah, Azrul Hakimi; Hashim, Mohamad Hasif; Hashim, Addam; Che Sabudin, Cik Muhamad Zafri (2019)
Technology Entrepreneurship is a project that search for problem or application for I technology, introduce new application and exploit opportunities that rely on science and technical. To get the high expectation in entrepreneurship knowledge, learn and research a r e important before starting a business. Thus, a case study is important to get the flow of business. Case study is the type of research design attempts to examine numerous characteristics of a person or group over extended period of time. Therefore, the outcome achieved by a case study are usually based on the example of one, the user cannot be certain as the generality. This study was performing to make some improvement and raise question for future research Basically, the background of our case study is to find the problem of Chef Tako having in producing their takoyaki and to find solution for their problem. There are several difficulties when their producing the takoyaki such as the production time of the sauce is taking so long because they don't have any machine to cool down the sauce. Besides that, Chef Tako having trouble in filling the sauce because the mechanism is ,t6~e)(pensive for Small and Medium Enterprise (SME). Moreover, packaging of the takoyaki flour also one of their hiccups because the plastic bag always leaks and affected their cost. Other than that, they also having lack of man power in their production line. So, we come out with several solutions to improve the difficulties of Chef Tako facing.